2022
DOI: 10.1093/humrep/deac068
|View full text |Cite
|
Sign up to set email alerts
|

De novo mutations in children born after medical assisted reproduction

Abstract: STUDY QUESTION Are there more de novo mutations (DNMs) present in the genomes of children born through medical assisted reproduction (MAR) compared to spontaneously conceived children? SUMMARY ANSWER In this pilot study, no statistically significant difference was observed in the number of DNMs observed in the genomes of MAR children versus spontaneously conceived children. WH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…Errors in DNA replication, exposure to mutagens, or failure to repair DNA damage can result in de novo mutations ( 12 ). Nowadays, advanced paternal age at conception has been considered the predominant factor associated with an increasing number of de novo mutations ( 9 , 11 , 42 , 43 ). However, in our study, the average paternal age at conception was 29.2 years, significantly younger than the data of the US ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Errors in DNA replication, exposure to mutagens, or failure to repair DNA damage can result in de novo mutations ( 12 ). Nowadays, advanced paternal age at conception has been considered the predominant factor associated with an increasing number of de novo mutations ( 9 , 11 , 42 , 43 ). However, in our study, the average paternal age at conception was 29.2 years, significantly younger than the data of the US ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Wong et al (44) reported that medically assisted conception would increase the incidence of de novo mutations compared with natural conception. However, recently, a pilot study by Smits et al (11) showed no impact of assisted reproductive technologies on the number of de novo mutations in the genome of the offspring. In our study, the majority of the pedigrees (98.04%) with de novo mutations were spontaneous conception, which limited us to investigate the impact of different methods of conception on de novo mutations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supplementary Table 9 Dataset from Smits et al, 2022 used to calculate the percentage of DNMs that have an iSNP within 5kb ranges.…”
Section: Supplementary Tablesmentioning
confidence: 99%
“…Cases where an iSNP could not be found in the coding region had primers designed to cover 5 kb regions around the DNM position for parent and proband samples (Figure 1.b3). We chose the 5 kb region based on the analysis of 4344 DNMs identified in 53 whole genome sequenced individuals/children (Smits et al, 2022). This revealed the presence of at least 1 iSNP within 5 kb of any given DNM in 81% of cases (Supplementary Tables 8 and 9).…”
Section: Target Amplification Groupsmentioning
confidence: 99%